Full ground ultra-wideband wearable textile antenna for breast cancer and wireless body area network applications - Mahmood, S.N. (MDPI AG, 2021)
Wireless body area network (WBAN) applications have broad utility in monitoring patient health and transmitting the data wirelessly. WBAN can greatly benefit from wearable antennas. Wearable antennas provide comfort and continuity of the monitoring of the patient. Therefore, they must be comfortable, flexible, and operate without excessive degradation near the body. Most wearable antennas use a truncated ground, which increases specific absorption rate (SAR) undesirably. A full ground ultra-wideband (UWB) antenna is proposed and utilized here to attain a broad bandwidth while keeping SAR in the acceptable range based on both 1 g and 10 g standards. It is designed on a denim substrate with a dielectric constant of 1.4 and thickness of 0.7 mm alongside the ShieldIt conductive textile. The antenna is fed using a ground coplanar waveguide (GCPW) through a substrate-integrated waveguide (SIW) transition. This transition creates a perfect match while reducing SAR. In addition, the proposed antenna has a bandwidth (BW) of 7â28 GHz, maximum directive gain of 10.5 dBi and maximum radiation efficiency of 96, with small dimensions of 60 Ã 50 Ã 0.7 mm3 . The good antennaâs performance while it is placed on the breast shows that it is a good candidate for both breast cancer imaging and WBAN. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.